A facilely synthesized lactam acceptor unit for high-performance polymer donors. Issue 6 (13th January 2017) - Pan, Han; Xiao, Zuo; Xie, Fangyuan; Li, Qifang; Ding, Liming
Abstract : A lactam acceptor unit BDTP i was developed. PThBDTP i :PC71 BM solar cells gave a PCE of 8.11%, indicating that BDTP i is a promising building block for D–A copolymers. Abstract : An aromatic lactam acceptor unit, [2, 2′-bidithieno[3, 2- b :2′, 3′- d ]pyridine]-5, 5′(4 H, 4′ H )-dione (BDTP i ), was developed for making D–A copolymer donors. Two D–A copolymers, PThBDTP i and PSeBDTP i, gave power conversion efficiencies (PCEs) of 8.11% and 6.50%, respectively, when using PC71 BM as the acceptor.